Using Show and Tell (S&T) Method to Improve Speaking Skills of Grade Eight Students of Junior High School - Nurul, Syarifah; Erniwati; Mochtar Marhum; Mashuri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research aims to find out if using of Show and Tell (S&T) Method can improve students’ speaking skills of Junior High School. This research used quasi-experimental design that consisted of two groups; experimental and control group. The samples of this research were grade eight students of Junior High School; VIII A. Ki Hajar Dewantara with 31 students as the experimental group and VIII E. Kapitan Pattimura with 32 students as the control group that selected by using simple random sampling. The data was collected by administering a test consisted of the pre-test and the post-test that conducted at first and last meetings. Then the treatment was only given to the experimental group. The result of experimental group’s pre-test is 36.29, while control group is 37.10. The result of experimental group’s post-test is 59.27, while control group is 47.26. By applying 0.05 level of significance, the researcher found that the value of the t-counted (4.50) is higher than the t-table (1.67). In conclusion, the use of Show and Tell (S&T) Method is effective to improve students’ speaking skills of Junior High School.